Factors Related to Injury in Youth and Adolescent Baseball Pitching, with an Eye Toward Prevention. (May 2015) - Popchak, Adam; Burnett, Thomas; Weber, Nicholas; Boninger, Michael
Abstract : ABSTRACT: The baseball and medical communities have recognized injuries of the upper extremity associated with the overhead throwing motion and have examined manners in which to reduce risk. The authors examine special features of the adolescent pitcher as compared with skeletally mature pitchers and characteristics of pitch mechanics, type, velocity, fatigue, and overuse. A summary is presented on previously identified risk factors as they relate to pitching injuries. Development, use, and compliance with the most current pitching guidelines in youth baseball, based on the available evidence, will be presented and examined. In an increasingly competitive environment, identifying known risk factors and potential signs of pathology as well as implementing the current best evidence in a consistent manner are important steps in decreasing injury risk of youth baseball pitchers. More research is needed to evaluate the effectiveness of pitching guidelines in the short and long term and to focus on manners in which to increase compliance with best practice procedures throughout youth baseball organizations.